Cutaneous lymphocyte antigen expression loss and PD1 positivity in early cutaneous lesions of rapidly progressive mycosis fungoides. Issue 5 (15th September 2014) - Ogunrinade, Olakunle; Ahn, Christine S.; Gergis, Usama; Yassin, Aminah H.; Magro, Cynthia
Key Clinical Message: It's important to assess cases both clinically and pathologically for factors potentially predictive of an aggressive clinical course. We concluded that the relative immunosuppressive effects of PD1 may contribute to tumor progression while the lack of staining for cutaneous lymphocyte antigen may be an additional factor facilitating distant extracutaneous migration. Abstract : It's important to assess cases both clinically and pathologically for factors potentially predictive of an aggressive clinical course. We concluded that the relative immunosuppressive effects of PD1 may contribute to tumor progression while the lack of staining for cutaneous lymphocyte antigen may be an additional factor facilitating distant extracutaneous migration.